MUSLIMS DEPICTION IN HOLLYWOOD MOVIES: A QUALITATIVE STUDY - Uzma Kiran; Dr Ayesha Qamar; Dr Malik Adnan; Dr Enaam Youssef Mohammed Youssef (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The September 11 attacks have dramatically shifted the spotlight of mainstream media and Cinema to Muslims in covering their socio-cultural norms. The Cinema developed a new theme of War films that usually projects Muslims as adversaries. As a result, the negative sentiments regarding Muslims and Islam have risen significantly in the Western world. In this researcher, we analyzed Hollywood films released after 9/11 using standard content analysis. In this qualitative research, we explored several facets of Muslim identity, including those related to depictions of Muslims. The findings reveal that Hollywood movies mainly represented Muslims as antagonistic to Western values concerning women’s rights, intolerance, and oppression. The research found that movies made in Hollywood perpetuate Islamophobic rhetoric. According to the projections seen in films, Hollywood helps fuel anti-Muslim prejudice, often known as Islamophobia. As a result, this study looked at Hollywood’s involvement in sticking to socio-political reasons by looking into films that are capable of creating interest in and discussion about the largely unfavorable representation of Muslims. We recommend future research on the comparative analysis of Hollywood War films before the War on terror, during the War on Terror, and the process of induction to Islamophobic discourse.